Food culture and development of tourism - Novakov, Marina; Gligić, Perica; Janković, Snežana (Economics of Agriculture, 2010)
This paper analyzes socio-cultural component of nutrition and the importance of the food and wine as part of a market of cultural tourism. Also, the paper reviews on development of tourism which has, from former privileges of minorities, become a mass phenomenon, and the signifcance of viticulture in our country through centuries.